PREPARATION OF MANGANESE DIOXIDE MODIFIED GLASSY CARBON ELECTRODE BY A NOVEL FILM PLATING/CYCLIC VOLTAMMETRY METHOD FOR H(2)0(2) DETECTION - WEN-ZHI,LE (Sociedad Chilena de Química, 2009)
Manganese dioxide modified glassy carbon electrode (Mn0(2)/GC) was prepared by a novel film plating/cyclic voltammetry method for the determination of H(2)0(2). A manganese film was first cathodically deposited on the surface of glassy carbon electrode from MnCl2 solution at the potential of-1.4 V versus Ag/ AgCl (satd. KC1), and then a well defined manganese dioxide was deposited on the surface of glassy carbon electrode by cyclic voltammetry at potential range -0.6 ~ 0.6 V, scan rate 100 mV s-1 in 0.1 mol L7¹ NaOH solution. The resulted modified electrode was characterized by cyclic voltammetry and scanning electron microscopy (SEM), which showed excellent electrocatalytic activity for the oxidation of H(2)0(2). The chronoamperometric detection of H(2)0(2) was carried out at 0.6 V in phosphate buffer solution pH 7.38 containing 0.1 mol L7¹ KC1 and the linear relationship of response current on H(2)0(2) concentration was obtained in the range from 4. Ixl0~10 to lxl0~-mol L-1 with a minimum detectable concentration of 3xl0~10 mol L7¹ [S/N (signal noise ratio) = 3]. The response time of the electrode to achieve 95% of the steady-state current was < 2 s. No measurable reduction in analytical performance of the modified electrode was found by storing the electrode in ambient conditions for 30 days. This modified electrode has many advantages such as simple preparation procedure, remarkable catalytic activity, good reproducibility and long term stability of signal response during hydrogen peroxide oxidation. The deposition of manganese dioxide on the surface of GC appears to be a highly efficient method for the development of a new class of sensitive, stable and reproducible hydrogen peroxide electrochemical sensor.